From Mining Sites to Mining Data: Archaeology's Future. Issue 1 (5th November 2015) - Schlanger, Sarah; Wilshusen, Richard; Roberts, Heidi
Abstract : Some 40 years after the field of cultural resource management was conceived, the most surprising consequence may be that the sheer quantity of archaeological observations made by the field's practitioners has far outstripped our ability to synthesize information and make those synthetic studies available to key interests, including government archaeologists, cultural resource management professionals, and the academy. Here we revisit the key proposals put forward in Bill Lipe's Conservation Model for American Archaeology, published in Kiva in 1974, to provide context for understanding the present and the future of cultural resource management and archaeological research. We see today's "conservation crisis" as a crisis in data management and call for a fundamental transformation in how we think about archaeological data and how we educate and train archaeologists in order to secure a productive future for cultural resource management and for the field of archaeology as it is practiced in North America.